Use of Kyiv Caves by Bats (Chiroptera): Hibernation and Swarming - Godlevskaya, E.V. (Вестник зоологии, 2007)
Представлены результаты наблюдений рукокрылых в подземельях Киева в 1999–2006 гг. Обследовано 28 объектов, относящихся к четырем типам: сакральным рукотворным пещерам, лессовым природным пещерам, оборонным сооружениям и дренажным штольневым системам (ДШС). Из 4 типов убежищ рукокрылыми в наибольшей степени используются ДШС. В них обнаружены относительно крупные зимовочные скопления — до 269 особей в одном объекте. Доминантом зимних скоплений рукокрылых в осмотренных подземельях является M. daubentonii — 97,4% общего количества всех учтенных особей. Остальные 2,6% представлены M. dasycneme, M. mystacinus, P. auritus. Весеной рукокрылые начинают покидать штольни не позднее конца марта с пиком приблизительно в середине апреля. Для ДШС зарегистрировано явление осеннего роения, во время которого отмечено 5 видов рукокрылых: M. daubentonii, M. dasycneme, M. mystacinus, P. auritus и E. serotinus (доминантом является первый вид — 97,4%). We present results of bat observation in the underground cavities of Kyiv and vicinities carried out in 1999–2006. In the studies we examined 28 objects of four different types (sacral artificial caves, loess natural caves, desolated military constructions, and drainage gallery systems (DGS)). We found that DGS were the most used by bats. In one of the DGS we counted up to 269 specimens. The dominant of the hibernation aggregations was M. daubentonii — 97.4% of found individuals. The rest 2.6% was represented by M. dasycneme, M. mystacinus, P. auritus. We discovered that bats start departing DGS no later than the end of March, with the departure peak falling at the middle of April. We observed autumn swarming by the DGS. Totally, five species were registered in the swarming: M. daubentonii, M. dasycneme, M. mystacinus, P. auritus and E. serotinus. Again the dominant species was M. daubentonii — 97.4% of individuals captured.